2016
DOI: 10.1007/s10072-015-2420-x
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of association between SNCA, HUSEYO and CSMD1 gene variants and Parkinson’s disease in Iranian population

Abstract: Parkinson's disease (PD) is the second most prevalent neurodegenerative disorder. Both genetic and environmental factors are involved in the etiology of the disease. Many studies have revealed the susceptibility genes and variations for PD which need further confirmation. Here we evaluated the association of variations in SNCA, HUSEYO and CSMD1 genes with PD. A case-control study was conducted with 489 PD patients and 489 healthy controls. DNA was extracted from peripheral blood of all subjects and rs356220 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…8,9 CSMD1 gene variants have also been associated with Parkinson's disease. 10 These results indicated the involvement of CSMD1 in nerve system disease. Moreover, research on CSMD1 mainly focuses on carcinoma.…”
Section: Introductionmentioning
confidence: 81%
“…8,9 CSMD1 gene variants have also been associated with Parkinson's disease. 10 These results indicated the involvement of CSMD1 in nerve system disease. Moreover, research on CSMD1 mainly focuses on carcinoma.…”
Section: Introductionmentioning
confidence: 81%
“…According to the results of whole-exome sequencing analysis performed on two Spanish families diagnosed with PD, it has been suggested that mutations in the CSDM1 gene may cause the familial PD phenotype [ 58 ]. However, a study conducted on the Iranian population showed no association between CSMD1 rs12681349 polymorphism and PD [ 59 ]. A case-control study conducted on the Han population in northern China in 2021 showed that polymorphisms in the CSMD1 gene were closely related to PD, and significant differences were found in rs10503253 and rs1983474 polymorphisms between PD cases and controls.…”
Section: Csmd1 Functionmentioning
confidence: 99%
“…Studies have shown that α‐synuclein plays an important role in the regulation of polysynaptic function and plasticity, as well as in the release of neurotransmitters from dopaminergic neurons 13 . In the past decades, many studies have focused on the relationship between the single nucleotide polymorphisms (SNPs) within SNCA gene and PD susceptibility, 14‐16 and there are 39 different SNPs in SNCA gene, and it has been proved that some SNPs have statistical significance on PD susceptibility. Some SNPs have been studied wildly, such as rs356219, which located at 3’region, but some SNPs are not well studied, perhaps in Chinese Han population, such as rs2301134, rs2301135 and rs356221.…”
Section: Introductionmentioning
confidence: 99%